A Rare Case of Retroperitoneal Schwannoma: A Case Report (Indian Journal of Case Reports, 2021)
Abdominal schwannomas are a very rare entity and retroperitoneal schwannomas even more so. Here, we present the case of a 59-year-old male. The patient presented with undiagnosed intermittent pain abdomen. Workup and imaging revealed a well-defined solid cystic mass in the retroperitoneal lumbar region compressing the inferior vena cava. There was no evidence of disseminated disease. Laparotomy was done and the mass was excised. Histological examination revealed a benign schwannoma. The patient had an uneventful post-operative period and was discharged and is currently on follow-up.